Disharmoni Keluarga Ditinjau dari Intensitas Komunikasi - Nisfi Laili Munawaroh; Nur Azizah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2018)
A harmonious family is the most beautiful treasure in the life of the world. A harmonious family can be a wonderful spirit to do everything. But sometimes life in the family will find problems. So that harmonious family atmosphere is often eroded by these problems. Actually, every problem will find the right solution if a family can communicate intensely. This study focuses on family disharmony in terms of communication intensity. This study uses a qualitative approach to the type of case study research. The subjects of this study were DT, WI, LL, SG, LM, ES, and HT. In data collection, this research uses observation and interview method. The data presented is obtained by doing field observation directly with the support of interviews with the related subjects. The data are analyzed data and then presented in the form of words, then analyzed to be ta ken conclusion as the result of research. After the researcher conducted the initial observation and found the family who in the disharmonic condition in Karangpucung village, Purwokerto Selatan subdistrict, the writer do deeper observation and interview related to family disharmony in terms of communication intensity. The results showed that the intensity aspects of communication in DT and WI families were: 1) attention during communication, 2) regularity, 3) message width, and 4) message depth. In addition, the intensity of communication factors in DT and WI families are 1) self-image and image of others, 2) psychological atmosphere, 3) physical environment, 4) tendency to lead together, and 5) dislike trust as a telling place between DT and WI.